Penerapan Model Pembelajaran Kooperatif Tipe Think Pair Share Untuk Meningkatkan Hasil Belajar IPA Siswa: Indonesia - Herawati (Sekolah Tinggi Ilmu Tarbiyah Al- Kifayah Riau, 2021)
This study aims to improve students' science learning outcomes using the Think Pair Share Cooperative learning model. This research was conducted in two cycles and each cycle was conducted in two meetings. For this research to run well, the researcher arranged the stages in classroom action research, namely planning, action research, action observation, and reflection. The subjects in this study were teachers and students of Class V Elementary School 011 Desa Baru, totaling 40 people. Data collection techniques were carried out by observation, documentation, and test techniques. The results showed that the application of Think Pair Share Type Cooperative learning can improve student learning outcomes. These results can be seen from the first cycle of student success reaching 64.7% and in the second cycle increasing to 91.18% with the 'Very Good' category. This proves that the application of Think Pair Share Type Cooperative learning can improve students' science learning outcomes. The results of the study can be seen from the increase in learning outcomes in the first cycle which increased to 31 students who finished studying or 77.5% with an average grade of 68.25. The average value of the class is quite good and meets the success indicator, namely 65. In the second cycle, it increased sharply to 38 students who finished studying or 95% with the class average score of 84.25.